Paranoie fasciste? Il volontariato in favore dell’Etiopia durante la guerra del 1935-1936 - João Fábio Bertonha è Dottore in Storia sociale presso l’Universidade Estadual de Campinas (UNICAMP). Specialista in temi strategici internazionali presso la National Defense University (EUA), è professore di Storia contemporanea presso l’Universidade Estadual de Maringá/PR (Brasile) e ricercatore del CNPq. È autore di molte opere, tra cui più di una decina di libri, nell’ambito degli studi sul fascismo, le relazioni internazionali, la difesa, l’immigrazione, la storia d’Italia e quella degli Stati Uniti. (Diacronie. Studi di Storia Contemporanea, 2013)
This paper focuses on the fascist fear that the government of Addis Abeba could recruit a force of volunteers to help in the resistance to the Italian invasion in 1935-1936. Despite the evidence that such a possibility was remote, the Italian diplomacy kept a watchful eye on the development of a volunteer force, in Europe as well as in the Americas and in the Middle East. This is an indication that such fears were amplified by broader issues, such as Italy’s pro-Arab politics, the risks of the Italian antifascist mobilization and the uprising of colonized peoples and/or black people.